Teaching children with dyslexia : a practical guide - Ott, Philomena (New York : Routledge, 2007)
Offers advice to teachers on how to recognize the specific learning difficulties associated with dyslexia, discusses synthetic and analytic phonics, and explains the importance of a working relationship between home and school and other topics.
Includes bibliographical references (p. [269]-290) and index.
Professional
Keywords: Dyslexic children -- Ability testing; Dyslexic children -- Education; Ability -- Testing; Dyslexic children -- Education